Characterization and Antimicrobial Activity of Postbiotic from Lactobacillus Acidophilus LA5 on Staphylococcus Aureus in Food Model and In vitro - Khani, Nader; Soleimani, Roya Abedi; Rad, Aziz Homayouni (Current Nutrition & Food Science, 2025)
BackgroundPostbiotics, also called biogenics, metabiotics, or Cell-Free Supernatants (CFS), are soluble compounds produced by live probiotic microorganisms or released after the lysis of probiotics that could provide beneficial health effects to the host.ObjectiveThis study was conducted with the aim of investigating the antimicrobial, antibiofilm, antioxidant, and cytotoxic effects of postbiotics derived from Lactobacillus acidophilus.MethodsIn this study, the antimicrobial properties of the postbiotic of L. acidophilus on Staphylococcus aureus were investigated in different experimental settings, in-vitro, and pasteurized milk. The antioxidant effect of postbiotic was also evaluated by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 20-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) method. Furthermore, the chemical composition of the postbiotics was identified via gas chromatography-mass spectrometry. The cytotoxic effects of the compounds were investigated using a human normal cell line.Results and DiscussionAccording to the results, postbiotics had aconcentration-dependent antimicrobial effect, and the inhibitory effect increased with increasing concentrations. The antimicrobial activity was mainly linked with lactic acid and laurostearic acid. The Minimum Inhibitory Concentration (MIC) of the prepared postbiotic was determined to be 100 mg/ml. The lowest Minimum Effective Concentration (MEC) of postbiotics significantly differed in the food matrix, and a low MEC (minimum effective concentration) index (150 mg/ml) was detected for postbiotic of L. acidophilus.ConclusionTherefore, the prepared postbiotic should be subjected to more in-depth analysis to examine its suitability as a food additive.
Keywords: lactic acid